Rhizobium - Trichoderma interaction in vitro and in vivo - R. RAMABADRAN, J. JAYARAJ and (Indian Phytopathology, 2002)
The interaction between Rhizoctonia and Trichoderma harzianum was investigated in vitro and under field conditions in Tamil Nadu, India. The individual growth of Rhizoctonia and T. harzianum was significantly affected in dual culture. In field testsa slight increase in Vigna mungo seed yield was recorded.